Avanços e desafios na/para a produção de materiais didáticos (pedagógicos) para o uso no ensino remoto - ALMEIDA, Carolina Gonçalves de (2024)
This course conclusion work presents and discusses the results of a study carried out with teachers who participated in the digital classes project carried out by Inteleleri Tecnologia para Educação, a Google Partner company, in partnership with the Department of Education of Ananindeua. Therefore, this study has the question of the challenges faced in the production of teaching materials for remote teaching by teachers who attended training courses developed by Inteleleri, in partnership with SEMED. As objectives, we had to identify challenges faced by teachers of Basic Education, Initial Years, for the production of teaching materials for remote education and show advances from these productions. Methodologically, it is a quanti-qualitative research, with a questionnaire, available as an electronic form, for the constitution of empirical data. The collaborators were 20 teachers from two public schools in the city of Ananindeua-PA. The results indicate as main challenges the different realities regarding access to technologies by students and the lack of equipment. As for the difficulties, the limitation regarding internet access and communication with parents stood out. As positive aspects, the flexibility of schedules and activities and the possibility of preparing and providing varied and interactive activities were indicated. Furthermore, the participation of teachers in the project enabled the development of teaching materials in the different digital tools studied, with Google Form being the most used.